Investigation On Factors Of Children Mobility Commuting To Schools By Walking From The Parent’s Perspective - Talan, Donny; . A . Khalifa, Nasradeen (Recent Trends in Civil Engineering and Built Environment, 2021)
Walking is claimed as the best mode to school due to its benefits towards environment and health. Currently, there are many safety and environmental issues had become decisive factors that preventing the parents to allow their children from walking. Several investigations showed that walking as a mode choice continues to suffer from narrow and weak foundations. To address this issue, this article aims to , in order to identify factors affecting the parents’ decision about walking to school, and to conceptualize the relationship between different factors that affecting on parents’ decision (i) investigate the parent’s decision on allowing their children mobility to school by walking. (ii) determine what are the main factor thet affecting parent’s decision on allowing their children mobility to school by walking. (iii) investigate are the aware of the consequences of their decision, This research found that factors such as Distance Environment Infra, Traffic,Weather, and Gender’ perception have great influence in parents’ decision to allow their children walking to and from school. Thus, national programs have to address the safety, traffic, and environmental issues such as traffic lights, pedestrian crossing improvements, and walking or bicycle paths to reduce parents concern. The findings of this Study can be used to better deal with parents’ concern about their children to travel actively and safely to school.